The inflammasome in host response to biomaterials: Bridging inflammation and tissue regeneration. (1st January 2019) - Vasconcelos, Daniela P.; Águas, Artur P.; Barbosa, Mário A.; Pelegrín, Pablo; Barbosa, Judite N.
Graphical abstract: Abstract: The development of new biomaterials to be used in tissue engineering applications is creating new solutions for a range of healthcare problems. The trend in biomaterials research has shifted from biocompatible "immune-evasive" biomaterials to "immune-interactive" materials that modulate the inflammatory response supporting implant integration as well as improving healing and tissue regeneration. Inflammasomes are large intracellular multiprotein complexes that are key players in host defence during innate immune responses and assemble after recognition of pathogens or danger signals. The process of biomaterial implantation causes injury to tissues that will consequently release danger signals that could be sensed by the inflammasome. There are increasing evidences that the inflammasome has a role in several inflammatory processes, from pathogen clearance to chronic inflammation or tissue repair. Thus, modulation of the inflammasome activity appears as an important target in the development of effective approaches in regenerative medicine. In this review, we discuss the main points of the current understanding on the host response to implanted biomaterials and how the paradigm of "immune-evasive" biomaterials has shifted over the last years; the significance of the inflammasome in the inflammatory response to biomaterials; and the growing idea that the immune system is of key importance in an effective tissue repair and regeneration. Statement of significance: We herein discuss the main points of the current understanding on the host response to implanted biomaterials and how the paradigm of "immune-evasive" biomaterials has shifted to "immune-interactive" over the last years; the significance of the inflammasome in the inflammatory response to biomaterials; and the growing idea that the immune system is of key importance in an effective tissue repair and regeneration, supporting the emerging concept of Regenerative Immunology. The inflammasome is a recent and central concept in immunology research. Since the beginning of this century the inflammasome is viewed as key platform of the innate immune response. We believe that, successful modulation of the inflammasome activity will become a milestone in the fields of tissue engineering and regenerative medicine.